Impact Of Storytelling On Knowledge Sharing For Higher Education Learning - Lee, Chen Kang (2007)
This research study examines the impact of storytelling on knowledge sharing in higher educational venues. Specifically, this study acted as an initial exploratory study in order to analyze and create an understanding regarding the impact of storytelling in contributing to the knowledge sharing in higher education learning focused on one of the private universities in Malaysia.